ETHICAL CONSEQUENCES OF MODERN HUMAN RESOURCE MANAGEMENT PRACTICES: A STUDY OF THE INFLUENCE OF JUSTICE ORGANIZATION TO REPUTATION COMPANY IN PT. SSP MOROWALI CENTRAL SULAWESI - Nur Indah; Baharuddin Semmaila; H.Baso Amang; Hj.Aryanti Arfah; Muhammad Arif; Tenri Wahyu (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the ethical consequences of implementing modern human resource management practices, specifically examining the influence of organizational justice dimensions on the formation of corporate reputation. in PT. SSP Morowali, acompany Which operate in region Central Sulawesi. Method study use approach quantitative with design survey. Sample studyThe sample consisted of 120 employees selected using simple random sampling. The data were analyzed using multiple linear regression analysis. The results showed that, both partially and simultaneously, the dimensions of distributive justice, procedural justice, and interactional justice had a positive and significant influence on corporate reputation. Findings This indicates thatimplementation principle justice as runway ethical in human resource management not only impact on welfare employees, but also become strategic factors in building public image and trust in the company. This research contributes to the development of ethical human resource management and serves as a management consideration in formulating sustainable policies oriented towards enhancing the organization's reputation.